Farewell to Virtual Environments and Welcome to Post-pandemic Mathematical Problem Posing and Solving - Silvera Alarcón, Edwin Neil (2023)
In the classrooms, teachers faced the dilemma of whether or not to use virtual environments to continue teaching, because students were able to pose and solve mathematical problems with the help of ICT. The objective is to analyze the student's perspectives when applying real situations, remote real situations and situations from the mathematical poem to solve the posing and solving of mathematical problems. The methodology is descriptive, quantitative, exploratory and observational, with a sample of 72 elementary school students. Resulting significant effects and positive acceptance of the methodology. In Conclusion students no longer used virtual environments and ICT to pose and solve mathematical problems.